2016
DOI: 10.1080/02755947.2015.1116472
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Northern Pike on Stocked Rainbow Trout in Pactola Reservoir, South Dakota

Abstract: Establishment of nonnative Northern Pike Esox lucius in Pactola Reservoir, South Dakota, has prompted concern among biologists about the influence of this species on the lake's intensively managed salmonid fisheries. Ancedotal information suggests that catch rates of Rainbow Trout Oncorhynchus mykiss have declined while mean size and abundance of Northern Pike has increased, although quantitative information on diet and growth of the Northern Pike population is lacking. To address potential interactions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…(ii)Implementation: referring to whether the cost estimate was actually realised in the invaded habitat (observed) or whether it was extrapolated (potential). For example, potential costs can include estimated reductions in shery income (Scheibel et al, 2016), known local costs that are extrapolated to a larger system in which they occur (Oreska and Aldridge, 2011), and costs extrapolated over multiple years based on estimates from a shorter period (Leigh, 1998);…”
Section: Global Cost Descriptionsmentioning
confidence: 99%
“…(ii)Implementation: referring to whether the cost estimate was actually realised in the invaded habitat (observed) or whether it was extrapolated (potential). For example, potential costs can include estimated reductions in shery income (Scheibel et al, 2016), known local costs that are extrapolated to a larger system in which they occur (Oreska and Aldridge, 2011), and costs extrapolated over multiple years based on estimates from a shorter period (Leigh, 1998);…”
Section: Global Cost Descriptionsmentioning
confidence: 99%
“…Invasive alien species are also responsible for a variety of substantial losses across many socio-economic sectors (Bacher et al 2018). As an illustration, it has been shown that a reduction of 10-16% of yield crops globally was associated with invasive insects (Bebber et al 2013), but invasive species can also cause losses of human-made goods and services (Binimelis et al 2007), destruction of infrastructure over sectors like forestry (Scheibel et al 2016), fisheries (Rosaen et al 2012), and agriculture (Paini et al 2016), among others. Such sectors often drive the economy of a country, and the effects of biological invasions can hinder its sustainable economic growth, especially in developing countries (Early et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, stocked fish are actually suppressing wild production that would have naturally occurred (Youngson and Verspoor, 1998). Similarly, pen-raised fish may not be well suited for wild release, which ultimately relegates these stocking events to very costly and unnecessary dietary supplementation for established wild populations (Pouder et al, 2010;Scheibel et al, 2016). Thus, the value of provisioning services may not change despite large sums of money invested.…”
Section: Fish-stock Enhancementmentioning
confidence: 99%